The Effects of Traditional Medical Practices on Health Care Delivery System in Nigeria. Quantitative Case Study of Ibiaku Issiet Community of Akwa Ibom State, Nigeria - Olsson , Imaobong; Akpan , Ndu Ekpenyong (Journal of Social Science Studies, 2023)
This research investigates the factors influencing the persistent use of traditional medicine and its implications for the acceptance and utilization of modern healthcare in the urban local government area of Ibiaku Issiet, Akwa Ibom State, Nigeria. Sociologists and medical sociologists have expressed concerns about the continued reliance on traditional healers, which often disregards modern scientific methods and facilities. A sample of 150 respondents was randomly selected, and data was collected using a structured questionnaire. The study reveals that the high cost of modern healthcare is a significant challenge rural dwellers face, leading them to seek more affordable traditional medicine. Traditional remedies have effectively catered to the sociocultural preferences and aspirations associated with modern medical care. Nigeria's socio-economic and sociocultural context, characterized by beliefs in witchcraft, spirits, and gods as causes of diseases, make eradicating this deeply rooted cultural heritage futile. Consequently, individuals are more likely to prefer modern medicine to traditional treatment methods. Based on the findings, it is recommended that traditional medicine be granted legal recognition and co-recognition as an official healthcare system in Nigeria. There is a pressing need to enhance the status, funding, and facilities of traditional medical clinics and practitioners and develop comprehensive training programs.